The life cycle of large igneous provinces - Black, B; Karlstrom, L; Mather, T (Springer Nature, 2021)
Extremely voluminous magmatic systems known as Large Igneous Provinces (LIPs) punctuate Earth’s history, and the gases they release plausibly link large-scale geodynamic and magmatic processes with major climate shifts in Earth’s geological record. However, quantifying the relationships between magmatism, gas release, and environmental changes remains challenging. In this Review, we explore the major insights and outstanding questions regarding the linked evolution of mantle melting, expansive magmatic systems, and the redistribution of volatiles from the solid Earth to the atmosphere. The evolution of mantle melt generation during LIP episodes sets the fundamental tempo of magma emplacement throughout the crust. The progression of crustal LIP magmatism and associated hydrothermal activity help shape the chemical evolution of the continental lithosphere and surface environment. Prolonged exhalation of magmatic and metamorphic volatiles can decouple the tempo of gas release—a potential key driver of environmental changes—from the tempo of extrusive volcanic activity. LIPs demonstrate how large-scale magmatic systems interact with the surrounding lithosphere to drive evolving regimes of magma and volatile transfer through the crust. New, temporally resolved constraints on the evolution of LIP plumbing systems are needed to keep pace with increasingly precise timelines of paleoenvironmental change during LIP emplacement.